Aproveitamento de águas pluviais para uso pessoal - Gomes, Leonardo Sucupira (Universidade Federal Rural do Semi-Árido, 2017)
Water scarcity is a worrying factor for the panorama of the distribution of water on the planet, in the Brazilian territory and especially in the semi-arid region, it’s the lack of an irreplaceable resource that affects socially, ecologically and economically the whole region. One of the ways to preserve water is by using storing cisterns. With the use of rainwater, it is possible to dedicate a rational use of this water to domestic activities, where it will help in the economy of the houses that acquire this method of capture and storage. Removing the first millimeter of the captured water, it is suitable for human use. The first millimeter is studied and then easily eliminated from the water that will be reserved for use. Through the collection of rainwater, we remove its first millimeter, where it will be discarded impurities and products that can’t be used for people who will consume the water. A rainwater harvesting system was proposed through the use of cistern systems in a family residence, where it was possible to show that during a year, the water used domestically, the monthly and annual cost of the family in relation to the Water consumption supplied by the dealership company decreased. Making the use of cisterns viable for any type of residence, mainly to the ones located in semi-arid regions that go through a longer period of drought. Finally, it shows how much can be saved and how it can be built, both economically and ecologically, when family income is changed. Improving its hydrologic, economic and social conditions.
Use of rainwater for personal use
Keywords: Captação; Aproveitamento; Utilização; Economia; Capitation; Exploitation; Rainwater use; Economy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA